DAMPAK DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Nabilah, Azmi; Handayani, Avivah Sri; Putri, Amelia (Fakultas Ekonomi Universitas Djuanda, 2025)
This study aims to determine the impact of discipline and work motivation on employee performance. The research approach uses a quantitative method with data collection techniques through questionnaires. In determining the sample, nonprobability sampling with a purposive sampling approach was used. The research population consisted of 79 employees, who were also used as the research sample based on the Slovin formula calculation. Data analysis was performed through normality tests, linearity tests, and significance tests (t-tests) to test the research hypothesis. The t-test results for the discipline variable showed a t-count value of 4.197, which was greater than the t-table value of 1.960, so H0 was rejected. This finding shows that work discipline has a significant effect on employee performance. Furthermore, the results of the linearity test on the work motivation variable on employee performance showed a significance value of 0.811, higher than the significance limit of 0.05. Thus, it can be concluded that work motivation has a direct effect on employee performance, thereby fulfilling the prerequisites for further testing in the regression model. Overall, this study proves that both work discipline and work motivation are important factors that influence employee performance at the Daarul Qur'an Islamic Boarding School in Tangerang City.